Arrangement analysis of the Chinese learner’s dictionaries in Malaysia - Ho, Wee Chee; Chan, Jie Yan; Chong, Pei Qi; Neo, Yee Feng; Lee, Chi Heng (Journal of Chinese Language and Culture Studies, 2023)
With the growing numbers of Chinese language learners in Malaysia, Chinese language is getting more and more important. The importance and usage of Chinese learner’s dictionaries have also been revealed. However, there are still room for improvement on the development of Chinese learner’s dictionaries in Malaysia. Therefore, this article compared and analyzed the arrangement of structure and definition of four existing Chinese learner’s dictionaries in Malaysia. The comparative analysis in this article were divided into two parts: 1) comparison and analysis of the structural arrangement, and 2) comparison and analysis of the definition arrangement. The items of structural arrangement comparison included: table of contents, preface, instruction, abbreviation table, copyright page, radical index, index, appendix, and reference materials. The items of definition arrangement comparison included: vocabulary, sentence examples, Hanyu Pinyin, Chinese characters’ stroke order, HSK related vocabularies, and pictures. At the end of this research, a suggestion on the structural and definition arrangement of the Chinese learner’s dictionary is provided based on the analysis results.